Acquittals at the International Criminal Tribunal for the former Yugoslavia (ICTY) in 2012-2013: the domestic implications - Vukpalaj, Anton (Studies of Transition States and Societies, 2018)
From November 2012 to May 2013, the International Criminal Tribunal for the Former Yugoslavia (ICTY) rendered its verdicts in four trials involving eight former Croatian, Kosovo, and Serbian military, police and intelligence officials. These acquittals drew the attention of politicians, human rights organisations and victims’ associations, each for different reasons. This article focuses on internal political contexts in Croatia, Serbia and Kosovo, following the return of the acquitted officials to their countries. It analyses the use of these verdicts by domestic political elites to legitimise their exclusive narratives of war and shows that these verdicts will be used to achieve goals quite different from those envisaged by international tribunals. The reactions to the acquittals will be analysed as a manifestation of conflicting national political contexts, resulting from a combination of multiple factors between local, national and international actors.